Importance and Implementation Strategies of Systems Medicine Education in India - Durjoy Majumder; Dibyendu Kumar Ray; Ishita Chatterjee; Ranjan Kumar Gupta; Abhik Mukherjee; Tarun Kanti Naskar1; Probir Kumar Dhar; Asesh Banerjee (Annals of Systems Biology - Peertechz Publications, 2016)
Though the inevitable outcome of Systems Biology (SB) may be directed to seek answers to the medical problems; however, due to its expanding horizon and flexibility, different academic institutions across the globe focus on different aspects of SB in their educational curriculum. Hence, some European educationists propose for streamlining of different course curriculum. Here such issues are discussed with respect to their translation towards medicine and health care system i.e., Systems Medicine (SM) under the perspectives of developing countries. Conventional molecule centric highthroughput technology driven practices of SB that are being carried out in Western world may not fit under the perspective of developing countries due to associated high cost. Streamlining approach for SB course curriculum would shift the multi-/interdisciplinary (MDID) framework of SB towards more rigidity and narrow down the scope for the development of the subject in developing countries. Since independence of India, policy was adopted so that field dependent (FD) cognition has got priority.Present educational policy makers are trained with that direction; hence, they remain ignorant about the importance of other facets of education. Still there is some unawareness regarding the long-term effect about the implemented policy for country's development. Practice of SM is the need of time to address the regional and local problems. Development of domain knowledge and analytical methods should be prioritized for developing countries. This would invariably take an initiative towards further development of computational methods, information and web technology and automation; thereby its vastness and expanding horizons would be appreciated. Such activities may also shift the existing health care paradigm in near future. Learning process and education on SM through research could be the ideal path for the development of the subject. This, in turn, may blur the demarcating lines across and between the far disciplines and make a paradigm shift in the educational system across the globe.